Retrospective analysis of the development of the social and professional structure of the population in the Republic of Tuva - Samba, Anna D.-B. (The New Research of Tuva, 2022)
The article examines the history of the formation of the social and professional structure in the population of the Republic of Tuva, starting from the second half of the 19th century and until today. There are four stages in this process, each of which is considered in terms of the features of the social and professional structure of the population. Results of research published in academic papers of different years were used for the analysis of stages 1–3. In order to characterize the current situation, the author relies on the results of sociological studies in the Republic of Tuva. She took part in these studies as a member of the research team under the guidance of Z. T. Golenkova at the Institute of Sociology, FCTAS, RAS in 2019 and 2021 (in 2019, the sample size was 2,860 people; in 2021 — 1,536 people).At the first stage of social development, from the second half of the 19th c. to the late 1920s, three social strata were distinguished in society: the upper social class (princes, etc.), the middle social class (officials and independent arats); the lower social class (constantly dependent arats and the poor). From 1921 to the 1940s, the beginnings of a social and professional division appeared. From 1944 to the 1990s, the structure of society was already becoming more complicated, divisions were appearing within social strata, and groups were being distinguished. There was also a decrease in the number of people engaged in traditional forms of economy. Since the 1990s, the social and professional structure has become noticeably more complicated and differentiated.
Keywords: social structure; social and professional structure; social process; Tuvan society; occupation; professional group; social stratification; social stratum; Tuva; Tuvans